2022
DOI: 10.3389/fphys.2022.1004863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined aerobic and resistance training on gut microbiota and cardiovascular risk factors in physically active elderly women: A randomized controlled trial

Abstract: Background: Exercise can modulate gut microbiota and lower the risk of cardiovascular disease (CVD). However, the association between exercise-induced changes in gut microbiota and CVD risk have not been investigated.Objective: This study determined the effects of exercise training on CVD risk and gut microbiota in physically active elderly women and whether exercise-induced gut microbiota changes were associated with CVD risk.Methods: An 8-week randomized controlled trial was conducted with 14 elderly women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Shin discussed the relationship between the Proteobacteria phylum and the gut flora ecological balance [60], declaring that Proteobacteria could be regarded as a marker of disorder in the GM community and a potential diagnostic criterion for diseases. Here, the abundance of Proteobacteria phyla displayed a reduction in six studies among the seven studies that mentioned it [14,18,21,29,33,37,39]. However, a slight increase in Proteobacteria was detected in elite athletes engaging in strenuous exercise, which might result from the negative impact on the GM because of overloaded or prolonged training.…”
Section: Other Representative Bacteriamentioning
confidence: 84%
See 1 more Smart Citation
“…Shin discussed the relationship between the Proteobacteria phylum and the gut flora ecological balance [60], declaring that Proteobacteria could be regarded as a marker of disorder in the GM community and a potential diagnostic criterion for diseases. Here, the abundance of Proteobacteria phyla displayed a reduction in six studies among the seven studies that mentioned it [14,18,21,29,33,37,39]. However, a slight increase in Proteobacteria was detected in elite athletes engaging in strenuous exercise, which might result from the negative impact on the GM because of overloaded or prolonged training.…”
Section: Other Representative Bacteriamentioning
confidence: 84%
“…Furthermore, the type of intervention was also an important factor in the association with the microbial diversity index [29]. According to the results of this review, the coordinated intervention of varied exercise patterns showed a significant effect on the microbial diversity index of adults [20,21]. Hence, people participating in various sports events might gain a higher flora diversity than those performing a simplex pattern of exercise intervention.…”
Section: Changes In Microbial Diversity Indexmentioning
confidence: 88%
“…Candidatus Stoquefichus and Holdemania both belong to the Erysipelotrichaceae family, have been associated with heightened intestinal inflammation. Existing research highlights a plausible link between Holdemania and glucose and lipid metabolism disorders ( Zhong et al, 2022 ; Lippert et al, 2017 ; T; Zhao et al, 2021 ; Biassoni et al, 2020 ). The study indicates that fructose-induced colitis was accompanied by increased Holdemania abundance, concomitant with s suppressed ZO-1 expression and increased LPS levels ( Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“… Kulecka et al 26 (2020) Polish elite athletes (endurance sports) 16S Prevotella, and Veillonella genus ↑ / Increase the diversity of gut microbes and optimize the structure of gut microbes. Zhong et al 27 (2022) Elderly women 16S Alpha diversity; members of the order Coriobacteriales; Asaccharobacter, Collinsella and Fusicatenibacter↑; risk of metabolic syndrome↓ 8-week exercise training Regulate the structure of gut microbes, reduce the risk of CVD, and enhance physical functions. Wu et al 28 (2023) Middle-aged and elderly people in China 16S BP and heart rate levels ↓, immune-inflammatory factors (IL-6, IL-10) ↓, F/B ratio ↓, abundance of Escherichia-Shigella ↓, Bacteroides ↑ 12 weeks of LZJ training.…”
Section: Different Hypertension Concomitant Factorsmentioning
confidence: 99%
“…These metabolites have biological activities such as anti-inflammatory and antioxidant properties that can directly or indirectly influence BP regulatory mechanisms. 27 In addition, forms of exercise through harmonising the breath have shown significant positive effects in the treatment of hypertension. Among them, Liuzijue training (LZJ), a traditional exercise therapy that integrates breathing meditation with physical activity, has unique advantages in the prevention and improvement of hypertension.…”
Section: Different Hypertension Concomitant Factorsmentioning
confidence: 99%